Evaluation of Employee Performance in the Secretariat Field of the Department of Community and Village Empowerment of Pasuruan Regency - Rossa Ilma SIlfiah; Hambali; Rinda Nikmatun Nisak (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Performance evaluation is an assessment of the work results or achievements attained by an organization, team, or individual. Conducting performance evaluations can help identify areas for improvement. The Secretariat of the Community and Village Empowerment Office in Pasuruan Regency has a low professionalism index, which is due to issues within the performance dimensions of the ASN (State Civil Apparatus). These dimensions include the assessment of Employee Performance Targets (SKP) and the work behavior of ASN employees, as well as identifying programs that have not been implemented. This study aims to evaluate employee performance using Robbins' theory of dimensions and performance indicators, which include: Quality, Quantity, Responsibility, Cooperation, and Initiative. It also seeks to identify the supporting and inhibiting factors of employee performance in the Secretariat of the Community and Village Empowerment Office of Pasuruan Regency. The study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research results show that employee performance is still not optimal when viewed from Robbins' theory in (Mangkunegara, 2015). Supporting factors include the majority of employees being competent and the continuous updating of the application system. However, inhibiting factors include an insufficient number of human resources, poor communication between policymakers and employees, and the absence of technical training (BIMTEK) for updated or new applications